An Analysis of Derivational and Inflectional Morpheme in Selected News From Tempo.Co (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2020)
The objectives of this research are to know the derivational and inflectional morphemes and to know the functions of morpheme in the selected news from Tempo.co. This research uses qualitative method. The analysis shows that the derivational and inflectional morphemes found in Tempo.co as 357 words. Derivational shows 97 data (27.17 %) and inflectional shows 260 data (72.83 %). Derivational changes the grammatical categories of words which consists of suffix and prefix, for example, noun-forming suffix changes the words/morphemes to nouns in the suffix â€“ion, -ment, -ist, -ship and â€“er. Adjective-forming suffix changes the words/ morphemes to adjectives in the suffix â€“able, -al, -ful, -ic, -cal, and â€“ous. Adverb-forming suffix changes the words/morphemes to an adverb in the suffix â€“ly. While, verb-forming prefix changes adjective to new adjective or form verb to new verb in the prefix un- and mis-. The inflectional does not change the grammatical categories of words which consists of â€œ-s, -â€˜s, -er, -est, -s, -ed, -ing, and â€“enâ€. The suffix â€“s means plural. The suffix -â€˜s, -sâ€™ means possessive. The suffix â€“er means comparative. The suffix â€“est means superlative. The suffix â€“ed means past. The suffix â€“ing means Ving (continuous). The suffix â€“en means participle.